2016
DOI: 10.1002/eco.1733
|View full text |Cite
|
Sign up to set email alerts
|

Responses of ground‐dwelling arthropods to surface flow drying in channels and adjacent habitats along Mediterranean streams

Abstract: Intermittent streams are dynamic ecosystems that alternate between dry and wet states. Despite their global dominance, we have scant information about the effects of surface flow drying on terrestrial arthropods in channel and adjacent terrestrial habitats. In the present study, we used pitfall traps to characterise the terrestrial arthropod assemblages along lateral gradients (channel, riparian, and upland habitats) in perennial and intermittent reaches of two contrasting Mediterranean intermittent streams (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 42 publications
1
23
0
3
Order By: Relevance
“…Globally, TS research remains freshwater‐focussed, with few studies of dry‐channel ecology and fewer still that integrate terrestrial and aquatic components . Such integrative research is needed to improve understanding of spatiotemporal variability in community composition as ecosystems transition between lotic, lentic, and terrestrial states .…”
Section: Resultsmentioning
confidence: 99%
“…Globally, TS research remains freshwater‐focussed, with few studies of dry‐channel ecology and fewer still that integrate terrestrial and aquatic components . Such integrative research is needed to improve understanding of spatiotemporal variability in community composition as ecosystems transition between lotic, lentic, and terrestrial states .…”
Section: Resultsmentioning
confidence: 99%
“…For example, in California, Mazor et al [118] demonstrated acceptable performance of current biomonitoring indices such as the Southern California Index of Biotic Integrity (IBI) for many intermittent streams. Moreover, innovative approaches, such as one based on terrestrial fauna [119,120] are being developed.…”
Section: Biomonitoring In Highly Variable Systemsmentioning
confidence: 99%
“…Although ground-dwelling arthropod communities frequently do not change during seasonal drying in intermittent river reaches (Corti & Datry, 2014;McCluney & Sabo, 2012;O'Callaghan, Hannah, Boomer, Williams, & Sadler, 2013), there is strong and significant divergence in composition between perennial and intermittent reaches in a variety of streams (Corti & Datry, 2016;Ellis, Crawford, & Molles, 2001;Sánchez-Montoya et al, 2016). Our study differs from prior work (e.g., Corti Ellis et al, 2001;Sánchez-Montoya et al, 2016) in that we examine community dissimilarity over spatial and seasonal gradients along multiple stream channels over multiple years and that we examine both nestedness and turnover components of beta diversity over this spatial gradient. Our study differs from prior work (e.g., Corti Ellis et al, 2001;Sánchez-Montoya et al, 2016) in that we examine community dissimilarity over spatial and seasonal gradients along multiple stream channels over multiple years and that we examine both nestedness and turnover components of beta diversity over this spatial gradient.…”
mentioning
confidence: 91%
“…Here, we build on this body of work and compare richness (alpha diversity) and differences in composition (beta diversity) at the landscape scale across a replicated set of stream channels with perennial headwaters and intermittent to ephemeral lower reaches. Our study differs from prior work (e.g., Corti & Datry, 2016;Ellis et al, 2001;Sánchez-Montoya et al, 2016) in that we examine community dissimilarity over spatial and seasonal gradients along multiple stream channels over multiple years and that we examine both nestedness and turnover components of beta diversity over this spatial gradient. Specifically, we aim to test whether nestedness or turnover explains dissimilarity in ground-dwelling riparian arthropod community composition along replicated gradients of streamflow permanence.…”
mentioning
confidence: 98%
See 1 more Smart Citation